Negative active material for secondary battery, preparation method of negative active material, positive pole piece, negative pole piece, secondary battery and electric device
By using porous carbon beams, including microcarbon tubes and nanocarbon tubes, as the negative electrode active material of lithium-ion batteries, the problem of lengthening of lithium-ion diffusion path in the battery is solved, and the kinetic performance is significantly improved.
Patent Information
- Application Number
- CN202311363735.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-22
AI Technical Summary
While increasing the amount of active substance coating, the existing lithium-ion batteries cause the diffusion path of lithium ions in the battery to lengthen, affecting the kinetic performance, especially secondary batteries with thick electrodes.
A porous carbon beam containing microcarbon tubes and nanocarbon tubes is used as the negative electrode active material, and is prepared by carbonizing wood raw materials and grinding treatment to provide a high-speed transmission path of electrons and ions.
The dynamic performance of the secondary battery is significantly improved, especially the secondary battery with thick electrodes, and the charging and discharging efficiency and energy density of the battery are improved.
Smart Images

Figure CN119864416A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a negative electrode active material for a secondary battery and a preparation method thereof, a positive electrode sheet, a negative electrode sheet, a secondary battery and an electrical device. Background Art
[0002] The statements herein merely provide background information related to the present application and do not necessarily constitute prior art.
[0003] In recent years, as the application scope of lithium-ion batteries has become more and more extensive, lithium-ion batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. In order to obtain higher energy efficiency and reduce the manufacturing cost of batteries, lithium-ion batteries are often designed to increase the mass proportion of active materials and reduce the use of auxiliary materials. However, while increasing the amount of active material coating, the thickness of the active material coating will inevitably increase, resulting in a longer diffusion path for lithium ions in the battery, hindering the performance of materials close to the current collector, and ultimately affecting the kinetic performance of the battery. Summary of the invention
[0004] The present application provides a negative electrode active material for a secondary battery and a preparation method thereof, a positive electrode sheet, a negative electrode sheet, a secondary battery and an electrical device to improve the kinetic performance of the secondary battery, especially significantly improve the kinetic performance of a secondary battery with a thick electrode.
[0005] In order to achieve the above object, the first aspect of the present application provides a negative electrode active material for a secondary battery, comprising a porous carbon bundle, wherein the porous carbon bundle contains micron carbon tubes and nano carbon tubes arranged in a direction perpendicular to the axial direction of the porous carbon bundle.
[0006] Therefore, by applying a porous carbon bundle containing both micron carbon tubes and nano carbon tubes to the preparation of electrode sheets, the walls of the micron carbon tubes and nano carbon tubes have extremely high electron conductivity, which can provide a fast electron transport channel to transmit electrons. The cavity of the micron carbon tubes can store active material particles, and the cavity of the nano carbon tubes can store electrolyte. Therefore, the porous carbon bundle can provide a high-speed transmission path for electrons and ions at the same time, thereby improving the kinetic performance of the secondary battery.
[0007] In some embodiments, the length of the porous carbon bundle is 0.01 μm-200 μm.
[0008] In some embodiments, the ratio of the number of carbon nanotubes to the number of carbon microtubes in the porous carbon bundle is (10-100):1, and can be optionally (20-50):1.
[0009] In some embodiments, the porous carbon bundle has at least one of the following features:
[0010] (1) The pore size of the carbon nanotubes in the porous carbon bundle is 1 nm-999 nm;
[0011] (2) The pore size of the micron carbon tubes in the porous carbon bundle is 1 μm-30 μm;
[0012] (3) The cross-sectional diameter of the porous carbon bundle is 0.01 μm-40 μm, optionally 0.1 μm-30 μm, and further optionally 0.1 μm-10 μm;
[0013] (4) The powder resistivity of the porous carbon bundle is 10 -3 Ω·m-10 -5 Ω·m.
[0014] In some embodiments, the negative electrode active material for secondary batteries comprises one or more of porous carbon bundles with a length of less than 1 μm, porous carbon bundles with a length of 1 μm-10 μm, porous carbon bundles with a length of 10 μm-30 μm, and porous carbon bundles with a length of more than 30 μm.
[0015] In some embodiments, the ratio of the number of porous carbon bundles with a length of less than 1 μm, the number of porous carbon bundles with a length of 1 μm-10 μm, the number of porous carbon bundles with a length of 10 μm-30 μm, and the number of porous carbon bundles with a length of more than 30 μm to the total number of porous carbon bundles contained in the negative electrode active material for a secondary battery is recorded as n1, n2, n3 and n4, respectively, and n1, n2, n3 and n4 satisfy: 0≤n1≤100%, 0≤n2≤100%, 0≤n3≤100% and 0≤n4≤100%, and n1, n2, n3 and n4 cannot be 0 at the same time;
[0016] Optionally, n1, n2, n3 and n4 satisfy: 5%≤n1≤40%, 5%≤n2≤60%, 5%≤n3≤50% and 0.1%≤n4≤30%.
[0017] The second aspect of the present application provides a method for preparing the negative electrode active material for a secondary battery according to the first aspect of the present application, comprising the following steps:
[0018] Carbonizing the wood raw material; the wood raw material has wood conduits arranged in a direction perpendicular to the axial direction of the wood raw material;
[0019] The carbonized wood raw material is ground to prepare the negative electrode active material for the secondary battery.
[0020] In some embodiments, the carbonization treatment includes at least one of the following conditions:
[0021] (1) The temperature of the carbonization treatment is 700° C.-900° C.;
[0022] (2) The carbonization treatment time is 2h-12h, and can be 4h-8h;
[0023] (3) The atmosphere of the carbonization treatment includes an inert gas;
[0024] Optionally, the atmosphere of the carbonization treatment includes argon.
[0025] In some embodiments, the grinding process includes at least one of the following conditions:
[0026] (1) The rotation speed of the grinding process is ≤300 rpm;
[0027] (2) The grinding time is ≤ 20 min.
[0028] In some embodiments, before the step of carbonizing the wood raw material, the step further includes:
[0029] Using alkali solution to perform alkali treatment on the wood raw material;
[0030] Optionally, the alkali solution includes at least one of a sodium hydroxide solution and a potassium hydroxide solution;
[0031] Optionally, the concentration of the alkali solution is 0.1mol / L-0.3mol / L;
[0032] Optionally, the alkali treatment time is 18h-30h.
[0033] In some embodiments, the wood feedstock comprises arbor pieces.
[0034] The third aspect of the present application provides a positive electrode sheet, the positive electrode sheet comprising a positive electrode active material layer, the positive electrode active material layer comprising at least one of the negative electrode active material for a secondary battery of the first aspect of the present application and the negative electrode active material for a secondary battery prepared by the method of the second aspect of the present application. The positive electrode sheet comprising a porous carbon bundle has excellent kinetic properties.
[0035] In some embodiments, the positive electrode active material layer further comprises a first conductive agent;
[0036] Optionally, the first conductive agent includes a zero-dimensional conductive agent;
[0037] Further optionally, the positive electrode active material layer has at least one of the following characteristics:
[0038] (1) The mass ratio of the negative electrode active material for secondary battery contained in the positive electrode active material layer to the first conductive agent is 1:(2-4);
[0039] (2) The total mass proportion of the negative electrode active material for secondary battery and the first conductive agent contained in the positive electrode active material layer is 1% to 10%;
[0040] (3) The first conductive agent includes a point-shaped contact conductive agent;
[0041] Optionally, the first conductive agent includes one or more of conductive carbon black, acetylene black and Ketjen black.
[0042] In some embodiments, the positive electrode plate has at least one of the following features:
[0043] (1) The thickness of the positive electrode active material layer is ≥ 0.1 mm, and can be selected to be 0.05 mm-0.3 mm;
[0044] (2) The coating unit surface density of the positive electrode sheet is ≥ 0.1g / 1540.25mm2, which can be 0.16g / 1540.25mm 2 -0.5g / 1540.25mm 2 .
[0045] The fourth aspect of the present application provides a negative electrode sheet, the negative electrode sheet comprising a negative electrode active material layer, the negative electrode active material layer comprising at least one of the negative electrode active material for a secondary battery of the first aspect of the present application and the negative electrode active material for a secondary battery prepared by the method of the second aspect of the present application. The negative electrode sheet comprising a porous carbon bundle has excellent kinetic properties.
[0046] In some embodiments, the negative electrode active material layer further comprises a second conductive agent;
[0047] Optionally, the second conductive agent includes a zero-dimensional conductive agent;
[0048] Further optionally, the negative electrode active material layer has at least one of the following characteristics:
[0049] (1) The mass ratio of the negative electrode active material for secondary battery and the second conductive agent contained in the negative electrode active material layer is (3-6):1;
[0050] (2) The total mass proportion of the negative electrode active material for secondary battery and the second conductive agent contained in the negative electrode active material layer is 0.1%-10%;
[0051] (3) the second conductive agent includes a point-shaped contact conductive agent;
[0052] Optionally, the second conductive agent includes one or more of conductive carbon black, acetylene black and Ketjen black.
[0053] In some embodiments, the negative electrode plate has at least one of the following features:
[0054] (1) The thickness of the negative electrode active material layer is ≥ 0.01 mm, and can be selected to be 0.1 mm-0.3 mm;
[0055] (2) The coating unit surface density of the negative electrode sheet is ≥ 0.05 g / 1540.25 mm2, which can be 0.16 g / 1540.25 mm 2 -0.5g / 1540.25mm 2 .
[0056] The fifth aspect of the present application provides a secondary battery, which includes at least one of the positive electrode plate of the third aspect of the present application and the negative electrode plate of the fourth aspect of the present application.
[0057] In some embodiments, the secondary battery includes at least one of a lithium ion battery and a sodium ion battery.
[0058] The sixth aspect of the present application provides an electrical device, comprising the secondary battery of the fifth aspect of the present application.
[0059] Details of one or more embodiments of the present application are set forth in the following drawings and description. Other features, objects, and advantages of the present application will become apparent from the specification, drawings, and claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] In order to better describe and illustrate the embodiments or examples provided by the present application, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered as limiting the scope of the disclosed application, the embodiments or examples currently described, and any of the best modes of these applications currently understood. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0061] Figure 1 It is a schematic diagram of a battery cell according to an embodiment of the present application.
[0062] Figure 2 for Figure 1 An exploded view of a battery cell according to an embodiment of the present application is shown.
[0063] Figure 3 It is a schematic diagram of a battery module according to one embodiment of the present application.
[0064] Figure 4 A schematic diagram of a battery pack according to an embodiment of the present application.
[0065] Figure 5 for Figure 4An exploded view of a battery pack according to an embodiment of the present application is shown.
[0066] Figure 6 FIG. 1 is a schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source.
[0067] Description of reference numerals:
[0068] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 cover plate; 6 electrical device. DETAILED DESCRIPTION
[0069] Below, some embodiments of the battery cells, secondary batteries and electrical devices of the present application are described in detail with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0070] "Scope" disclosed in the present application can be limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or excluding end values, and any end value can be included or not included independently, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 listed, and if the maximum range values 3,4 and 5 are also listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation for these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to listing the parameter as, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For example, when a parameter is expressed as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9 and 10.
[0071] In the present application, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0072] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0073] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. The "implementation methods" mentioned herein have a similar understanding.
[0074] Those skilled in the art will appreciate that, in the methods of each embodiment or example, the order in which each step is written does not mean a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.
[0075] In the present application, in the open technical features or technical solutions described by the words "contain", "include", "comprise", etc., unless otherwise specified, additional members other than the listed members are not excluded, and it can be regarded as providing both closed features or solutions consisting of the listed members and open features or solutions including additional members in addition to the listed members. For example, A includes a1, a2 and a3. Unless otherwise specified, it may also include other members or may not include additional members. It can be regarded as providing both the feature or solution of "A consists of a1, a2 and a3" and the feature or solution of "A not only includes a1, a2 and a3, but also includes other members". In the present application, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.
[0076] In this application, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If there are multiple "options" in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "option" is independent.
[0077] When the thickness of the active material layer in the positive electrode sheet and / or the negative electrode sheet in the lithium-ion battery increases, the dynamic performance of the battery will be affected. In response to the problems caused by thick electrodes, the relevant technologies usually improve the original design or adopt a step electrode manufacturing method, that is, use different combinations of slurries (usually different in conductivity or porosity) to coat multiple times to make thick electrodes; or try to add a transport channel or an electrolyte layer in the thickness direction of the thick electrode to ensure the performance of the thick electrode, both of which have certain disadvantages. Among them, the step electrode manufacturing method not only requires the configuration of different slurries, but also requires multiple coatings of different thicknesses, and the porosity is difficult to control, the process is complex, the design is difficult, and the difference in porosity of different layers causes different difficulties in the infiltration of the electrolyte, thereby affecting the distribution of the electrolyte in the thickness direction. In the method of adding a transport channel to the thick electrode, the diameter of the through hole reaches several microns or even tens of microns. In addition to the high technical difficulty of adding through holes, the coated electrode material is lost in the length and width directions of the pole piece, which is not worth the loss.
[0078] In response to the above problems, the present application provides a negative electrode active material for a secondary battery, which includes a porous carbon bundle. The porous carbon bundle also includes micron carbon tubes and nano carbon tubes. Through the combination of micron carbon tubes and nano carbon tubes, a high-speed transmission path for electrons and ions can be provided at the same time, thereby improving the kinetic performance of the secondary battery.
[0079] A first aspect of the present application provides a negative electrode active material for a secondary battery, comprising a porous carbon bundle, wherein the porous carbon bundle contains micron carbon tubes and nano carbon tubes arranged in a direction perpendicular to the axial direction of the porous carbon bundle.
[0080] It should be noted that porous carbon bundles refer to a plurality of carbon tubes with different pore sizes; micron carbon tubes refer to carbon tubes with a pore size of micrometer level, and nano carbon tubes refer to carbon tubes with a pore size of nanometer level. The negative electrode active material for secondary batteries only means that it may contain a plurality of porous carbon bundles, and does not limit the length and cross-sectional diameter of the porous carbon bundles contained therein. That is, the plurality of porous carbon bundles contained in the negative electrode active material for secondary batteries may have a relatively small difference in carbon bundle length and / or carbon bundle cross-sectional diameter, or may have a relatively large difference in carbon bundle length and / or cross-sectional diameter.
[0081] It can be understood that by applying a porous carbon bundle containing both micron carbon tubes and nano carbon tubes to the preparation of electrode sheets, the tube walls of the micron carbon tubes and nano carbon tubes have extremely high electron conductivity, which can provide a fast electron transport channel to transmit electrons, the cavity of the micron carbon tubes can store active material particles, and the cavity of the nano carbon tubes can store electrolyte, so that the porous carbon bundle can provide a high-speed transmission path for electrons and ions (such as lithium ions or sodium ions) at the same time, thereby improving the kinetic performance of the secondary battery.
[0082] It should be noted that the negative electrode active material for secondary batteries provided in the present application can be used in lithium-ion batteries as well as sodium-ion batteries.
[0083] In some embodiments, the length of the porous carbon bundle is 0.01 μm-200 μm; for example, it can be, but is not limited to, 0.01 μm, 0.03 μm, 0.05 μm, 0.08 μm, 0.1 μm, 0.3 μm, 0.5 μm, 0.7 μm, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, or a range between any two of the above values. When the length of the porous carbon bundle is within the above range, it is not easy to be broken during the cold pressing process of the secondary battery preparation, and has a better effect on improving the dynamic performance of the secondary battery.
[0084] As an example, the length of the porous carbon bundle mentioned above can be measured by the following method:
[0085] 1) Build the measurement optical path and collect data: Use a semiconductor laser with vertical polarization as the light source. The laser is focused along the x direction through a lens into the sample pool containing the porous carbon beam solution. The sample particles irradiated by the laser beam are scattered, and the scattered light I to be detected is V After passing through two facing pinholes, it shines on the Wollaston prism, which diffuses the light I V Decomposed into vertically polarized scattered light I VV and horizontal direction I VH The polarized scattered light is converted into electrical pulse signals H1 and H2 by the photomultiplier tube and the photomultiplier tube, and sent to the photon counting card for counting, while recording the scattering angle θ at this time;
[0086] 2) changing the incident direction of the laser irradiating the sample cell in a clockwise direction, that is, changing the incident direction of the laser by Δθ, repeating step 1) to collect data, collecting scattered light signals under different scattering conditions, and recording the corresponding scattering angles;
[0087] 3) Calculate the diameter and length of the porous carbon bundle:
[0088] A: The expression of the scattered light intensity autocorrelation function is as follows:
[0089]
[0090] Where τ is the correlation time, I(t) and I(t-τ) are the scattered light intensities at time t and time t-τ respectively, and n(t) and n(t-τ) are the numbers of scattered photons at the two times;
[0091] According to the expression, the experimental data is substituted into the autocorrelation function G of the scattered light intensity in two directions when the scattering angle is θ. VV-θ (τ) and G VH-θ (τ);
[0092] B: The scattered light autocorrelation function is an exponential decay function, in the form of the following formula, G VV-θ (τ) and G VH-θ (τ) The attenuation line width Γ of the autocorrelation function of the scattered light intensity in two directions is obtained by exponential fitting VV-θ and Γ VH-θ ,
[0093]
[0094] C: According to the relationship between Rayleigh line width and translation coefficient DT and rotation coefficient DR, calculate the translation coefficient DT and rotation coefficient DR:
[0095]
[0096] Where q(θ) is the scattering vector, and its calculation formula is as follows:
[0097]
[0098] Where n is the refractive index of the solution, λ0 is the wavelength of the incident light, and θ is the scattering angle;
[0099] D: Due to the translation coefficient D T and the rotation coefficient D R The porous carbon bundle diameter d and length L satisfy the following formula:
[0100]
[0101]
[0102] Where L is the length of the porous carbon bundle, d is the diameter of the porous carbon bundle, and k B is the Boltzmann constant, T is the absolute temperature, η sis the viscosity coefficient of the dispersion medium, which can be obtained by looking up the table. According to the above formula, the diameter d and length L of the porous carbon bundle are calculated;
[0103] 4) Data analysis and processing: Process the data results of the porous carbon bundle diameter and length calculated at different scattering angles θ to obtain the accurate diameter and length of the porous carbon bundle;
[0104] The specific steps of data analysis and processing are as follows:
[0105] 1) Obtaining the autocorrelation function of the collected scattered light signal. Since the depolarized scattered light signal decays faster than the polarized scattered light signal, the decay rate of the autocorrelation function is analyzed to determine whether there is an error in the collected signal;
[0106] 2) Compare the decay rates of the autocorrelation function of polarized scattered light and the autocorrelation function of depolarized scattered light at different scattering angles. The larger the sine value of the scattering angle, the greater the decay rate of the autocorrelation.
[0107] 3) Measure multiple groups of scattering vectors q(θ) at different scattering angles, and the attenuation line width Γ of the scattered light autocorrelation function VV-θ and Γ VH-θ , according to the Rayleigh line width and translation coefficient D T and the rotation coefficient D R The relationship between q(θ) is solved by the least square method. 2 and Γ VV-θ , Γ VH-θ Linear analysis: The translation coefficient D of the porous carbon bundle is obtained by linear analysis. R and the rotation coefficient D T , thus obtaining the diameter and length of the porous carbon bundle;
[0108] 4) Repeat the experimental steps 1)-3) 10 times, analyze and process the data to obtain 10 sets of measurement results, and calculate the average value of the 10 sets of data <l>and <d>, as the final result, the standard deviation of the experimental measurement repeatability is calculated according to the following formula,
[0109]
[0110] formula: <x>is the average of N experimental measurements, where N is the number of experiments.
[0111] In some optional embodiments, the ratio of the length of the porous carbon bundle to the thickness of the active material layer in the electrode piece is 0.2-1.
[0112] It should be noted that the active material layer in the electrode refers to the use of porous carbon bundles for the preparation of the active material layer of the positive electrode or for the preparation of the active material layer of the negative electrode. When the porous carbon bundle is used for the preparation of the active material layer of the positive electrode, the ratio of the length of the porous carbon bundle to the thickness of the active material layer of the positive electrode is 0.2-1; when the porous carbon bundle is used for the preparation of the active material layer of the negative electrode, the ratio of the length of the porous carbon bundle to the thickness of the active material layer of the negative electrode is 0.2-1.
[0113] In some embodiments, the number ratio of carbon nanotubes to micron carbon tubes is (10-100):1. When the number ratio of carbon nanotubes to micron carbon tubes is within the above range, the ion liquid phase transmission speed can be significantly improved without affecting the energy density of the pole piece. As an example, the number ratio of carbon nanotubes to micron carbon tubes can be but is not limited to 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, 50:1, 55:1, 60:1, 65:1, 70:1, 75:1, 80:1, 85:1, 90:1, 95:1, 100:1 or a range between any two of the above values. Optionally, the number ratio of carbon nanotubes to micron carbon tubes is (20-50):1.
[0114] As an example, the above-mentioned ratio of the number of carbon nanotubes to micron carbon tubes can be obtained by measuring the diameter of each carbon bundle and then performing statistics according to the above-mentioned method for measuring the length of porous carbon bundles, thereby further obtaining the ratio of the number of carbon nanotubes to micron carbon tubes.
[0115] In some embodiments, the pore size of the carbon nanotube is 1 nm-999 nm; for example, it can be, but is not limited to, 1 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, 850 nm, 900 nm, 950 nm, 999 nm, or a range between any two of the above values. When the pore size of the carbon nanotube is within the above range, sufficient liquid phase transmission channels for lithium ions can be provided.
[0116] It should be noted that for pole pieces using active materials with larger particles such as NCM ternary materials or graphite negative electrodes, the pore size of the carbon nanotubes is preferably 1nm-500nm; for pole pieces using active materials with small particle sizes such as lithium iron phosphate or lithium iron manganese phosphate, the pore size of the carbon nanotubes is preferably 1nm-100nm.
[0117] In some embodiments, the pore size of the micron carbon tube is 1 μm-30 μm; for example, it can be but not limited to 1 μm, 3 μm, 5 μm, 7 μm, 10 μm, 13 μm, 15 μm, 18 μm, 20 μm, 23 μm, 25 μm, 27 μm, 30 μm or a range between any two of the above values. When the pore size of the micron carbon tube is within the above range, active particles can be embedded or wrapped in the micron carbon tube, the micron carbon tube wall can provide an electron transmission channel, and the nano-carbon tubes around the micron carbon tube can provide a lithium ion liquid phase transmission channel, thereby improving the fast charging capability.
[0118] It should be noted that for pole pieces using active materials with larger particles such as NCM ternary materials or graphite negative electrodes, the pore size of the micron carbon tubes is preferably 3μm-150μm; for pole pieces using active materials with small particle sizes such as lithium iron phosphate or lithium iron manganese phosphate, the pore size of the micron carbon tubes is preferably 0.1μm-1μm.
[0119] As an example, the pore sizes of the above-mentioned carbon nanotubes and carbon microtubes can be measured using a scanning electron microscope (SEM), a transmission electron microscope (TEM), or an atomic force microscope (AFM).
[0120] In some embodiments, the cross-sectional diameter of the porous carbon bundle is 0.01 μm-40 μm; for example, it can be but not limited to 0.01 μm, 0.03 μm, 0.05 μm, 0.08 μm, 0.1 μm, 0.3 μm, 0.5 μm, 0.7 μm, 1 μm, 3 μm, 5 μm, 7 μm, 10 μm, 13 μm, 15 μm, 18 μm, 20 μm, 23 μm, 25 μm, 27 μm, 30 μm, 33 μm, 35 μm, 38 μm, 40 μm or the range between any two of the above values. When the cross-sectional diameter of the porous carbon bundle is within the above range, the micron carbon tubes can fully wrap the active material particles; at the same time, the porous carbon bundle will not occupy too much pole piece space, and the energy density of the pole piece will be less affected. Optionally, the cross-sectional diameter of the porous carbon bundle is 0.1 μm-30 μm. Further optionally, the cross-sectional diameter of the porous carbon bundle is 0.1 μm-10 μm.
[0121] As an example, the cross-sectional diameter of the porous carbon bundle mentioned above can be measured by a scanning electron microscope (SEM), a transmission electron microscope (TEM), or an atomic force microscope (AFM).
[0122] In some embodiments, the powder resistivity of the porous carbon bundle is 10 -3 Ω·m-10 -5 Ω·m; for example, but not limited to, 10 -3 Ω·m, 10 -4 Ω·m, 10 -5 Ω·m or the range between any two of the above resistivities.
[0123] As an example, the powder resistivity of the porous carbon bundle mentioned above can be measured using a powder resistance meter.
[0124] In some embodiments, the negative electrode active material for a secondary battery comprises one or more of a porous carbon bundle with a length of less than 1 μm, a porous carbon bundle with a length of 1 μm-10 μm, a porous carbon bundle with a length of 10 μm-30 μm, and a porous carbon bundle with a length of more than 30 μm. When the porous carbon bundles contained in the negative electrode active material for a secondary battery have multiple length ranges, the conductive and ion conductive paths can be matched, a three-dimensional transmission network can be constructed, and the electron and ion transmission speeds can be increased.
[0125] In some optional embodiments, the ratios of the number of porous carbon bundles with a length of less than 1 μm, the number of porous carbon bundles with a length of 1 μm-10 μm, the number of porous carbon bundles with a length of 10 μm-30 μm and the number of porous carbon bundles with a length of more than 30 μm to the total number of porous carbon bundles contained in the negative electrode active material for secondary batteries are recorded as n1, n2, n3 and n4, respectively, and n1, n2, n3 and n4 satisfy: 0≤n1≤100%, 0≤n2≤100%, 0≤n3≤100% and 0≤n4≤100%, and n1, n2, n3 and n4 cannot be 0 at the same time.
[0126] In some optional embodiments, n1, n2, n3 and n4 satisfy: 5%≤n1≤40%, 5%≤n2≤60%, 5%≤n3≤50% and 0.1%≤n4≤30%. When n1, n2, n3 and n4 are respectively within the above ranges, sufficient fast transmission channels can be established between adjacent particles, and fast transmission channels can also be established between multiple particles.
[0127] As an example, the length of the porous carbon bundles contained in the negative electrode active material for secondary batteries mentioned above, and the ratio of the number of porous carbon bundles whose lengths are in the above-mentioned ranges to the total number of porous carbon bundles contained in the negative electrode active material for secondary batteries can be measured by referring to the porous carbon bundle length determination method provided above, and then further statistics can be obtained to obtain the ratio of the number of porous carbon bundles whose lengths are in the above-mentioned ranges to the total number of porous carbon bundles contained in the negative electrode active material for secondary batteries.
[0128] The second aspect of the present application provides a method for preparing a negative electrode active material for a secondary battery according to the first aspect of the present application, comprising the following steps: carbonizing a wood raw material, the wood raw material having wood conduits arranged in a direction perpendicular to the axial direction of the wood raw material; grinding the carbonized wood raw material to prepare a negative electrode active material for a secondary battery.
[0129] It should be noted that the wood raw material has wood ducts arranged in a direction perpendicular to the axial direction of the wood raw material, which is conducive to retaining the duct system formed by ducts and sieve tubes existing in the wood raw material itself to the greatest extent, thereby facilitating the preparation of porous carbon bundles with micron carbon tubes and nano carbon tubes.
[0130] It can be understood that when preparing negative electrode active materials for secondary batteries, a screening process can be included after the grinding treatment to divide the porous carbon bundles according to the carbon bundle length to obtain a combination of porous carbon bundles containing one carbon bundle length range, two carbon bundle length ranges, three carbon bundle length ranges or four carbon bundle length ranges.
[0131] The method for preparing negative electrode active materials for secondary batteries provided in the present application uses wood as raw material, has low cost, simple preparation process and high preparation efficiency.
[0132] In some embodiments, the temperature of the carbonization treatment is 700°C-900°C; for example, it can be, but is not limited to, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C or a range between any two of the above values. When the temperature of the carbonization treatment is within the above range, the degree of graphitization of the porous carbon bundle obtained can be high, and its conductivity can be improved; at the same time, the probability of collapse of the microscopic pore structure of the wood raw material can be reduced.
[0133] In some embodiments, the carbonization treatment time is 2h-12h; for example, it can be but not limited to 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h or a range between any two of the above times. When the carbonization treatment time is within the above range, it can reduce the pore collapse of the porous carbon bundle and make the porous carbon bundle have a higher degree of carbonization and improve its conductivity. Optionally, the carbonization treatment time is 4h-8h.
[0134] In some embodiments, the atmosphere of the carbonization treatment includes an inert gas; alternatively, the atmosphere of the carbonization treatment includes argon.
[0135] As a possible implementation manner, the rotation speed of the grinding process is ≤300 rpm; when the rotation speed of the grinding process is within the above range, the damage to the microscopic pore structure of the wood raw material can be reduced.
[0136] As a possible implementation manner, the grinding treatment time is ≤20 min; when the grinding treatment time is within the above range, the damage to the microscopic pore structure of the wood raw material can also be reduced.
[0137] In some embodiments, before the step of carbonizing the wood raw material, the step further includes: performing an alkali treatment on the wood raw material using an alkali solution to wash away impurities or stains on the surface of the wood raw material.
[0138] In some optional embodiments, the alkali solution includes at least one of a sodium hydroxide solution and a potassium hydroxide solution.
[0139] In some optional embodiments, the concentration of the alkali solution is 0.1 mol / L-0.3 mol / L. When the concentration of the alkali solution is within the above range, it can effectively remove impurities or stains while reducing costs.
[0140] In some optional embodiments, the alkali treatment time is 18h-30h; for example, it can be but not limited to 18h, 19h, 20h, 21h, 22h, 23h, 24h, 25h, 26h, 27h, 28h, 29h, 30h or a range between any two of the above values. When the alkali treatment time is within the above range, the cost can be reduced while effectively removing impurities or stains.
[0141] In some optional embodiments, the wood raw material includes tree blocks. For example, when preparing the porous carbon bundle, a fresh tree trunk with a diameter of 5 cm to 10 cm and a length of about 30 cm can be selected, peeled, and then cut vertically along the radial direction into thin slices with a thickness of about 1 mm, and then the thin slices are divided into small wood blocks of 3 mm*3 mm for subsequent processing.
[0142] In some embodiments, the alkali-treated wood raw material is thoroughly washed with distilled water for several times and then dried in an oven at 100° C.-110° C. for 12 h.
[0143] In some embodiments, a method for preparing a negative electrode active material for a secondary battery comprises the following steps:
[0144] Select fresh tree trunks with a diameter of 5cm-10cm and a length of about 30cm;
[0145] Peel the bark, then cut it vertically into slices about 1 mm thick along the radial direction, and then divide the slices into 3 mm*3 mm pieces;
[0146] Then, the tree block is immersed in a 0.1mol / L-0.3mol / L alkaline solution for 18h-30h for alkaline treatment;
[0147] The alkali-treated tree blocks were thoroughly washed several times with distilled water and then dried in an oven at 100°C-110°C for 12 h;
[0148] The dried wood blocks were carbonized at 700-900°C in an argon atmosphere for 2h-12h;
[0149] The carbonized wood blocks are ground using a grinder to prepare negative electrode active materials for secondary batteries.
[0150] The third aspect of the present application provides a positive electrode sheet, which includes a positive electrode active material layer, the positive electrode active material layer includes at least one of the negative electrode active material for a secondary battery of the first aspect and the negative electrode active material for a secondary battery prepared by the method of the second aspect. The positive electrode sheet including the porous carbon bundle has excellent kinetic properties.
[0151] In some embodiments, the positive electrode active material layer further includes a first conductive agent.
[0152] In some optional embodiments, the first conductive agent includes a zero-dimensional conductive agent. Since the electronic conductivity of the positive electrode active material is poor, more zero-dimensional conductive agents are needed to adhere to the surface of the active material particles or fill the pores between the active material particles to construct a three-dimensional conductive network together with the porous carbon bundle. At the same time, the microscopic pores inside the porous carbon bundle can be infiltrated with the electrolyte to accelerate the liquid phase transmission of lithium ions.
[0153] In some optional embodiments, the mass ratio of the negative electrode active material for secondary battery and the first conductive agent contained in the positive electrode active material layer is 1:(2-4); for example, it can be but not limited to 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, 1:2.6, 1:2.7, 1:2.8, 1:2.9, 1:3, 1:3.1, 1:3.2, 1:3.3, 1:3.4, 1:3.5, 1:3.6, 1:3.7, 1:3.8, 1:3.9, 1:4 or a range between any two of the above ratios. When the mass ratio of the negative electrode active material for secondary batteries and the first conductive agent contained in the positive electrode active material layer is within the above range, the ion liquid phase transmission channel from the surface of the positive electrode plate to the positive electrode collector side can be effectively opened up, reducing or even avoiding the occurrence of increased liquid phase diffusion polarization; it can also establish electrical connections between the active material particles, reducing or even avoiding the occurrence of increased ohmic polarization.
[0154] In some optional embodiments, the sum of the mass proportions of the negative electrode active material for secondary batteries and the first conductive agent contained in the positive electrode active material layer in the positive electrode active material layer is 1%-10%; for example, it can be but not limited to 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10% or a range between any two of the above values. When the sum of the mass proportions of the negative electrode active material for secondary batteries and the first conductive agent contained in the positive electrode active material layer in the positive electrode active material layer is within the above range, the energy density and conductivity of the positive electrode sheet can be taken into account.
[0155] As an example, the mass ratio of the negative electrode active material for secondary battery and the first conductive agent contained in the positive electrode active material layer mentioned above, and the sum of the mass proportions of the negative electrode active material for secondary battery and the first conductive agent contained in the positive electrode active material layer in the positive electrode active material layer can be measured by the following method:
[0156] (1) Dry the powder of the positive electrode sheet to be tested under vacuum conditions to a constant weight and use it as a sample for later use;
[0157] (2) placing the powder obtained in step (1) into a crucible and placing it together with another empty crucible into a thermal analyzer;
[0158] (3) starting thermal analysis software to perform thermogravimetric analysis, thereby obtaining an accurate thermogravimetric curve and the ratio of the binder and the first conductive agent in the powder; wherein the heating rate is set to 2-20° C. / min, the heating range is set to 25-1000° C., and the test is started by passing an inert gas (at least one of helium, neon, argon, krypton, xenon, radon or nitrogen) or an air atmosphere or an oxygen atmosphere, and the atmosphere flow rate is 20-200 mL / min;
[0159] (4) The powder in step (1) is digested by an acid wet method (hydrochloric acid, nitric acid, or perchloric acid, etc.), the volume is fixed, and the content of each metal element therein is tested by inductively coupled plasma optical emission spectroscopy (ICP-OES) to determine the content of the negative electrode active material in the electrode, and the content of the binder and the first conductive agent in the powder is determined according to the ratio obtained in step (3).
[0160] In some optional embodiments, the first conductive agent includes a point contact conductive agent; optionally, the first conductive agent includes one or more of conductive carbon black, acetylene black and Ketjen black.
[0161] In some embodiments, the thickness of the positive electrode active material layer is ≥0.01 mm, and may be 0.05 mm-0.3 mm; for example, it may be but is not limited to 0.05 mm, 0.1 mm, 0.15 mm, 0.2 mm, 0.25 mm, 0.3 mm or a range between any two of the above thicknesses.
[0162] It should be noted that the thickness of the positive electrode active material layer mentioned in the present application refers to the thickness of the positive electrode active material layer located on one side of the positive electrode current collector.
[0163] As an example, the thickness of the positive electrode active material layer mentioned above can be measured by the following method: an optical microscope is used to obtain the ion polished cross-sectional morphology of the positive electrode electrode sheet, and then the thickness of the positive electrode active material layer is measured.
[0164] In some embodiments, the coating unit area density of the positive electrode sheet is ≥ 0.1 g / 1540.25 mm2, and can be 0.16 g / 1540.25 mm2. 2 -0.5g / 1540.25mm 2 ; For example, it can be but not limited to 0.16g / 1540.25mm 2 , 0.2g / 1540.25mm 2 , 0.25g / 1540.25mm 2 , 0.3g / 1540.25mm 2 , 0.35g / 1540.25mm 2 , 0.4g / 1540.25mm 2 , 0.45g / 1540.25mm 2 , 0.5g / 1540.25mm 2 Or the range between any two of the above coating unit surface densities.
[0165] As an example, the coating unit area density of the positive electrode sheet mentioned above can be measured by the following method: a plurality of positive electrode sheets with an area of 1540.25 mm 2 Weigh the small discs and take the average value.
[0166] It should be noted that the "first conductive agent" mentioned above is only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can it be understood as implicitly indicating the importance or quantity of the indicated technical features.
[0167] The positive electrode sheet also includes a positive current collector, and a positive active material layer is disposed on at least one surface of the positive current collector, and the positive active material layer contains a positive active material. As a non-limiting example, the positive current collector has two surfaces opposite to each other in its own thickness direction, and the positive active material layer is disposed on any one or both of the two opposite surfaces of the positive current collector.
[0168] In some of the embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the positive electrode current collector, non-limiting examples of the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the positive electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0169] In some embodiments, the positive electrode active material may also include one or more of a ternary material and a lithium iron manganese phosphate material; wherein the ternary material includes Lix(NiaCobMnc)1-dMdO2-yAy (x is 0.2-1.2) and / or LixAa(NiaCobMnc)1-dMdO2-yAy (x+a is 0.2-1.2); the lithium iron manganese phosphate material includes LiaMn1-yByP1-zCzO4-nDn (a is 0-1.1) and / or LiaAxMn1-yByP1-zCzO4-nDn (a+x is 0-1.1).
[0170] It should be noted that the above definition of x includes the molar content of Li under different charge and discharge states of the battery (usually the battery voltage is between 2-5V).
[0171] It is understandable that the battery will be accompanied by lithium (Li) deintercalation and consumption during the charging and discharging process, and the content of Li in the positive electrode plate is different when the battery is discharged to different states. In the list of positive electrode materials in this application, unless otherwise specified, the content of Li is the initial state of the material. The positive electrode material is applied to the positive electrode plate in the battery system, and after the charge and discharge cycle, the content of Li in the positive electrode material contained in the plate usually changes. Among them, the content of Li can be measured by molar content, but is not limited to this. Regarding "the content of Li is the initial state of the material", the initial state of the material refers to the state before the material is added to the positive electrode slurry. It is understandable that the new material obtained by appropriate modification on the basis of the listed positive electrode materials is also within the scope of the positive electrode material. The aforementioned appropriate modification refers to the acceptable modification method for the positive electrode material, and non-limiting examples include coating modification.
[0172] In the list of positive electrode materials in this application, the content of oxygen (O) is only a theoretical state value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual content of O will fluctuate. Among them, the content of O can be measured by molar content, but is not limited to this.
[0173] In some of the embodiments, the positive electrode active material may also use a positive electrode active material for a battery known in the art. As a non-limiting example, the positive electrode active material may also include one or more of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide (such as LiCoO2), lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds. Non-limiting examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. Non-limiting examples of lithium cobalt oxides may include LiCoO2; non-limiting examples of lithium nickel oxides may include LiNiO2; non-limiting examples of lithium manganese oxides may include LiMnO2, LiMn2O4, etc.; non-limiting examples of lithium nickel cobalt manganese oxides may include LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ) etc. Non-limiting examples of lithium nickel cobalt aluminum oxide may include LiNi 0.85 Co 0.15 Al 0.05 O2.
[0174] In some embodiments, the positive electrode active material includes a sodium ion active material.
[0175] As an example, the sodium ion active material may include one or more of the following materials: one or more of sodium transition metal oxides, polyanionic compounds, and Prussian blue compounds. However, the present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for sodium ion batteries may also be used.
[0176] As an optional technical solution of the present application, in the sodium transition metal oxide, the transition metal may include one or more of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. Non-limiting examples of sodium transition metal oxides may include Na x MO2, wherein M may include one or more of Ti, V, Mn, Co, Ni, Fe, Cr and Cu, 0<x≤1.
[0177] As an optional technical solution of the present application, the polyanionic compound can be a compound having sodium ions, transition metal ions and tetrahedral (YO4) n- A class of compounds with anionic units. Transition metals may include one or more of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y may be one or more of P, S and Si; n represents (YO4) n- valence state.
[0178] Polyanionic compounds can also be those with sodium ions, transition metal ions, tetrahedral (YO4) n- A class of compounds containing anion units and halogen anions. Transition metals may include one or more of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y may be one or more of P, S and Si, and n represents (YO4) n- valence state; the halogen can be one or more of F, Cl and Br.
[0179] Polyanionic compounds can also be sodium ions, tetrahedral (YO4) n- Anion unit, polyhedral unit (ZO y ) m+ and an optional halogen anion. Y can be one or more of P, S and Si, and n represents (YO4) n- valence state; Z represents a transition metal, which may include one or more of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; m represents (ZO y ) m+ valence state; the halogen can be one or more of F, Cl and Br.
[0180] Polyanionic compounds may include NaFePO4, Na3V2(PO4)3 (sodium vanadium phosphate, referred to as NVP), Na4Fe3(PO4)2 (P2O7), NaM'PO4F and Na3(VO y )2(PO4)2F 3-2y (0≤y≤1) or more. Wherein, M' in NaM'PO4F may include one or more of V, Fe, Mn and Ni.
[0181] Prussian blue compounds can be sodium ions, transition metal ions and cyanide ions (CN - ). The transition metal may include one or more of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. Non-limiting examples of Prussian blue compounds may include Na a Me b Me' c (CN)6, wherein Me and Me' can be independently one or more of Ni, Cu, Fe, Mn, Co and Zn, 0<a≤2, 0<b<1, 0<c<1.
[0182] In some of these embodiments, the positive electrode active material layer may also optionally include a binder. As a non-limiting example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0183] In some embodiments, the positive electrode active material layer may also optionally include other conductive agents known in the art for positive electrode plates, such as, for example, superconducting carbon, carbon dots, carbon porous carbon bundles, graphene, and carbon nanofibers.
[0184] In some of the embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the porous carbon bundle, the first conductive agent, the binder and any other components are dispersed in a solvent to form a positive electrode slurry; the positive electrode slurry is coated on at least one side of the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained. The type of solvent can be selected from but not limited to any one of the aforementioned embodiments, such as N-methylpyrrolidone (NMP). The surface of the positive electrode collector coated with the positive electrode slurry can be on a single surface of the positive electrode collector or on both surfaces of the positive electrode collector. The surface of the positive electrode collector coated with the positive electrode slurry can be on a single surface of the positive electrode collector or on both surfaces of the positive electrode collector. The solid content of the positive electrode slurry can be 40wt%-80wt%. The viscosity of the positive electrode slurry at room temperature can be adjusted to 5000-25000mPa·s. The compaction density of the positive electrode sheet can be 2-4g / cm 3 , optional: 3.3-3.5g / cm 3 .
[0185] A fourth aspect of the present invention provides a negative electrode sheet, the negative electrode sheet comprising a negative electrode active material layer, the negative electrode active material layer comprising at least one of the negative electrode active material for a secondary battery of the first aspect and the negative electrode active material for a secondary battery prepared by the method of the second aspect. The negative electrode sheet comprising the porous carbon bundle has excellent kinetic properties.
[0186] In some embodiments, the negative electrode active material layer further includes a second conductive agent.
[0187] In some optional embodiments, the second conductive agent includes a zero-dimensional conductive agent.
[0188] In some optional embodiments, the mass ratio of the negative electrode active material for secondary batteries and the second conductive agent contained in the negative electrode active material layer is (3-6):1; for example, it can be but not limited to 3:1, 3.3:1, 3.5:1, 3.8:1, 4:1, 4.3:1, 4.5:1, 4.8:1, 5:1, 5.3:1, 5.5:1, 5.8:1, 6:1 or a range between any two of the above ratios. When the mass ratio of the negative electrode active material for secondary batteries and the second conductive agent contained in the negative electrode active material layer is within the above range, the ion transmission channel from the surface of the negative electrode plate to the negative electrode current collector can be effectively opened, reducing the lithium plating caused by the local negative electrode on the surface of the plate during fast charging; it can also establish electrical connections between the active material particles, reducing or even avoiding the occurrence of increased ohmic polarization.
[0189] In some optional embodiments, the mass percentage of the negative electrode active material for secondary batteries and the second conductive agent contained in the negative electrode active material layer is 0.1%-10%; for example, it can be but not limited to 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10% or the range between any two of the above values. When the mass percentage of the negative electrode active material for secondary batteries and the second conductive agent contained in the negative electrode active material layer is within the above range, the energy density and conductivity of the negative electrode sheet can be taken into account.
[0190] As an example, the mass ratio of the negative electrode active material for secondary batteries and the second conductive agent contained in the negative electrode active material layer mentioned above, and the sum of the mass proportions of the negative electrode active material for secondary batteries and the second conductive agent contained in the negative electrode active material layer in the negative electrode active material layer can be measured by the following method:
[0191] (1) Dry the powder of the negative electrode sheet to be tested under vacuum conditions to a constant weight and use it as a sample for later use;
[0192] (2) placing the powder obtained in step (1) into a crucible and placing it together with another empty crucible into a thermal analyzer;
[0193] (3) starting the thermal analysis software to perform thermogravimetric analysis, thereby obtaining an accurate thermogravimetric curve and the ratio of the binder to the second conductive agent in the powder; wherein the heating rate is set to 2-20°C / min, the heating range is set to 25-1000°C, and the test is started by passing an inert gas (at least one of helium, neon, argon, krypton, xenon, radon or nitrogen) or an air atmosphere or an oxygen atmosphere, and the atmosphere flow rate is 20-200 mL / min;
[0194] (4) The powder in step (1) is digested by an acid wet method (hydrochloric acid, nitric acid, or perchloric acid, etc.), the volume is fixed, and the content of each metal element therein is tested by inductively coupled plasma optical emission spectroscopy (ICP-OES) to determine the content of the negative electrode active material in the electrode, and the content of the binder and the second conductive agent in the powder is determined according to the ratio obtained in step (3).
[0195] In some optional embodiments, the second conductive agent includes a point contact conductive agent; optionally, the second conductive agent includes one or more of conductive carbon black, acetylene black and Ketjen black.
[0196] In some embodiments, the thickness of the negative electrode active material layer is ≥0.01 mm, and may be 0.1 mm-0.3 mm; for example, it may be but is not limited to 0.1 mm, 0.15 mm, 0.2 mm, 0.25 mm, 0.3 mm, or a range between any two of the above thicknesses.
[0197] It should be noted that the thickness of the negative electrode active material layer mentioned in the present application refers to the thickness of the negative electrode active material layer located on one side of the negative electrode current collector.
[0198] As an example, the thickness of the negative electrode active material layer mentioned above can be measured by the following method: an optical microscope is used to obtain the ion polished cross-sectional morphology of the negative electrode electrode sheet, and then the thickness of the negative electrode active material layer is measured.
[0199] In some embodiments, the coating unit area density of the negative electrode sheet is ≥ 0.05 g / 1540.25 mm 2 , optional: 0.16g / 1540.25mm 2 -0.5g / 1540.25mm 2 ; For example, it can be but not limited to 0.16g / 1540.25mm 2 , 0.2g / 1540.25mm 2 , 0.25g / 1540.25mm 2 , 0.3g / 1540.25mm 2 , 0.35g / 1540.25mm 2 , 0.4g / 1540.25mm 2 , 0.45g / 1540.25mm 2 , 0.5g / 1540.25mm 2 Or the range between any two of the above coating unit surface densities.
[0200] As an example, the coating unit area density of the negative electrode sheet mentioned above can be measured by the following method: a plurality of negative electrode sheets with an area of 1540.25 mm 2 Weigh the small discs and take the average value.
[0201] It should be noted that the "second conductive agent" mentioned above is only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can it be understood as implicitly indicating the importance or quantity of the indicated technical features.
[0202] The negative electrode sheet also includes a negative electrode current collector, and a negative electrode active material layer is disposed on at least one surface of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material. As a non-limiting example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0203] In some of the embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the negative electrode current collector, non-limiting examples of the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the negative electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0204] In some of the embodiments, the negative electrode active material may adopt the negative electrode active material for batteries known in the art. As a non-limiting example, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include one or more of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0205] In some embodiments, the negative electrode active material layer may further include a binder. The binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0206] In some embodiments, the negative electrode active material layer may also optionally include other conductive agents known in the art for negative electrode plates. The conductive agent may include one or more of superconducting carbon, carbon dots, carbon porous carbon bundles, graphene, and carbon nanofibers.
[0207] In some of the embodiments, the negative electrode active material layer may further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0208] In some of the embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the porous carbon tube, the second conductive agent, the binder and any other components are dispersed in a solvent (a non-limiting example of the solvent is deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on at least one side of the surface of the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. The surface of the negative electrode collector coated with the negative electrode slurry can be on a single surface of the negative electrode collector or on both surfaces of the negative electrode collector. The solid content of the negative electrode slurry can be 40wt%-60wt%. The viscosity of the negative electrode slurry at room temperature can be adjusted to 2000-10000mPa·s. The compaction density of the negative electrode sheet can be 1.0g / cm 3 -1.8g / cm 3 .
[0209] The fifth aspect of the present application provides a secondary battery, comprising at least one of the positive electrode sheet of the third aspect and the negative electrode sheet of the fourth aspect. The secondary battery comprising the positive electrode sheet and / or the negative electrode sheet has excellent dynamic performance.
[0210] In some embodiments, the secondary battery includes at least one of a lithium ion battery and a sodium ion battery.
[0211] In addition, the secondary battery and the electric device of the present application will be described below with reference to the drawings as appropriate.
[0212] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0213] Electrolytes
[0214] The electrolyte has the function of conducting ions between the positive electrode and the negative electrode. The present application has no particular restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0215] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0216] In some of the embodiments, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0217] In some embodiments, the solvent may include ethylene carbonate (EC, ), propylene carbonate (PC, ), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate One or more of fluoroethylene carbonate (FEC), methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0218] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0219] In some embodiments, the additives in the electrolyte may include, but are not limited to, one or more of fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), and the like.
[0220] Isolation film
[0221] The present application has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.
[0222] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.
[0223] In some embodiments, the isolation film has a thickness of 1-40 μm, and optionally 5-20 μm.
[0224] In some of the embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly by a winding process or a lamination process.
[0225] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0226] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and further, non-limiting examples of plastic may include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0227] The secondary battery includes at least one battery cell. The secondary battery may include one or more battery cells.
[0228] In this application, unless otherwise specified, "battery cell" refers to a basic unit that can realize the mutual conversion of chemical energy and electrical energy, and further, generally speaking, at least includes a positive electrode sheet, a negative electrode sheet and an electrolyte. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting active ions between the positive electrode sheet and the negative electrode sheet.
[0229] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.
[0230] In some of these embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to actual needs.
[0231] The secondary battery may be a battery module or a battery pack.
[0232] The battery module includes at least one battery cell. The number of battery cells contained in the battery module can be one or more, and those skilled in the art can select a suitable number according to the application and capacity of the battery module.
[0233] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0234] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0235] In some of the embodiments, the battery modules may be assembled into a battery pack. The battery pack may contain one or more battery modules. Those skilled in the art may select a suitable number according to the application and capacity of the battery pack.
[0236] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0237] In addition, the present application also provides an electrical device, which includes at least one of the battery cell and the secondary battery provided in the present application. The secondary battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto. Among them, the mobile device may be, for example, a mobile phone, a laptop computer, etc.; the electric vehicle may be, for example, a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc., but are not limited thereto.
[0238] As an electrical device, a battery cell or a secondary battery can be selected according to its usage requirements.
[0239] Figure 6 The power consumption device 6 is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module can be used.
[0240] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0241] Example
[0242] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If the techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.
[0243] 1. Preparation of secondary batteries
[0244] Example 1
[0245] 1. Preparation of negative electrode active materials for secondary batteries
[0246] Select fresh tree trunks with a diameter of 5cm-10cm and a length of about 30cm, peel them, and then cut them vertically along the trunk radial direction into thin slices with a thickness of about 1mm, and then divide the thin slices into 3mm*3cm tree blocks; soak the tree blocks in 0.2mol / L NaOH solution for 24h for alkali treatment to wash away surface impurities or stains; wash the alkali-treated small wood blocks thoroughly with distilled water several times, and then dry them in an oven at 105℃ for 12h; then carbonize the tree blocks at 500℃ in an argon atmosphere. The carbonized wood block was ground with a grinder at a speed of 250 rpm for 15 min. The measurement showed that the porous carbon bundles with a length of less than 1 μm, 15.4% and 37.9% of the negative electrode active materials for secondary batteries obtained after the grinding treatment, respectively; the porous carbon bundles with a length of 1 μm-10 μm, 43.6% and 3.1% of the porous carbon bundles with a length of 10 μm-30 μm, respectively.
[0247] 2. Preparation of positive electrode
[0248] The negative electrode active material for the secondary battery prepared above is mixed with the positive electrode active material lithium iron phosphate, conductive carbon black, binder polyvinylidene fluoride, and dispersant polyacrylamide according to mass percentages of 0.75%, 95%, 2.25%, 1.8%, and 0.2%, respectively, and a solvent is added to make a slurry. Then, the positive electrode slurry is evenly coated on the two surfaces of the aluminum foil, and after drying, cold pressing, and cutting, a positive electrode sheet is obtained; wherein the thickness of the positive electrode active material layer is 0.15 mm, and the coating unit surface density of the positive electrode material is 0.38 g / 1540.25 mm 2 .
[0249] 3. Preparation of negative electrode sheet
[0250] The negative electrode active material for the secondary battery prepared above was mixed with negative electrode active material graphite, conductive carbon black, and a binder (styrene-butadiene rubber and sodium carboxymethyl cellulose in a mass ratio of 1:1) in the amounts of 1.6%, 96%, 0.4%, and 2% by mass, respectively, and a solvent was added to prepare a slurry. Then, the positive electrode slurry was evenly coated on both surfaces of the copper foil, and the negative electrode sheet was obtained after drying, cold pressing, and cutting. The thickness of the negative electrode active material layer was 0.13 mm, and the coating unit surface density of the negative electrode material was 0.162 g / 1540.25 mm 2 .
[0251] 4. Preparation of Electrolyte
[0252] In an argon atmosphere glove box, ethylene carbonate (EC, as a solvent), dimethyl carbonate (DMC, as a solvent), ethyl methyl carbonate (EMC, as a solvent), diethyl carbonate (DEC, as a solvent), vinylene carbonate (VC, as an additive), fluoroethylene carbonate (FEC, as an additive), toluene diisocyanate (TDI, as an isocyanate substance), lithium hexafluorophosphate (LiPF6, as a first lithium salt), and lithium bistrifluoromethanesulfonyl imide (as a second lithium salt) are mixed in percentage by mass to obtain an electrolyte.
[0253] 5. Isolation film
[0254] A polyethylene film is used as the isolation film.
[0255] 6. Preparation of soft pack batteries
[0256] The above-mentioned positive electrode plate, negative electrode plate and separator are assembled into a soft-pack battery, and a sufficient amount of electrolyte is injected, followed by formation and capacity separation to finally obtain a finished test soft-pack battery.
[0257] Example 2-22
[0258] The preparation method of the secondary battery in Examples 2-22 is basically similar to the preparation method of the secondary battery in Example 1, and the main differences are: at least one of the temperature of the carbonization treatment, the rotation speed of the grinding treatment, the time of the grinding treatment, the mass ratio of the porous carbon bundle to the first conductive agent in the positive electrode sheet and the mass ratio of the porous carbon bundle to the second conductive agent in the negative electrode sheet is different; the mass proportions of different carbon bundle length ranges in the prepared porous carbon bundle are different. The details are shown in Table 1.
[0259] The difference between Example 23 and Example 2 in preparing the negative electrode active material for secondary batteries is that screening is performed after grinding so that the prepared porous carbon bundle combination contains porous carbon bundles with a length of less than 1 μm, porous carbon bundles with a length of 1 μm-10 μm, and porous carbon bundles with a length of 10 μm-30 μm, and their quantity proportions are shown in Table 1.
[0260] The difference between Example 24 and Example 2 in preparing the negative electrode active material for secondary batteries is that screening is performed after grinding so that the prepared porous carbon bundle combination contains porous carbon bundles with a length of less than 1 μm, porous carbon bundles with a length of 1 μm-10 μm, and porous carbon bundles with a length of more than 30 μm, and their quantity proportions are shown in Table 1.
[0261] The difference between Example 25 and Example 2 in preparing the negative electrode active material for secondary batteries is that screening is performed after grinding so that the prepared porous carbon bundle combination contains porous carbon bundles with a length of less than 1 μm, porous carbon bundles with a length of 10 μm-30 μm, and porous carbon bundles with a length of more than 30 μm, and their quantity proportions are shown in Table 1.
[0262] The difference between Example 26 and Example 2 in preparing the negative electrode active material for secondary batteries is that screening is performed after grinding so that the prepared porous carbon bundle combination contains porous carbon bundles with a length of 1μm-10μm, porous carbon bundles with a length of 10μm-30μm, and porous carbon bundles with a length greater than 30μm, and their quantity proportions are shown in Table 1.
[0263] The difference between the preparation of the secondary battery positive electrode sheet in Example 27 and the preparation of the secondary battery positive electrode sheet in Example 1 is that the porous carbon bundles are replaced by carbon porous bundles (CNT) of the same mass.
[0264] The difference between the preparation of the secondary battery negative electrode sheet in Example 28 and the preparation of the secondary battery negative electrode sheet in Example 1 is that the porous carbon bundles (CNT) of the same mass are used to replace the porous carbon bundles.
[0265] Comparative Example 1
[0266] The difference between the preparation of the negative electrode sheet of the secondary battery in Comparative Example 1 and the preparation of the secondary battery in Example 1 is that the same mass of carbon porous carbon bundles (CNT) are used to replace the porous carbon bundles in the positive electrode sheet and the negative electrode sheet respectively.
[0267] The porous carbon bundles prepared in the above-mentioned embodiments were respectively tested for the following structural parameters: the ratio of the number of nano-carbon tubes to micro-carbon tubes in the porous carbon bundles, the degree of graphitization, and the cross-sectional diameter of the porous carbon bundles.
[0268] It should be noted that although the length of the carbon bundle is mainly related to the grinding time and the grinding speed, when the same grinding time and grinding speed are used in different embodiments, the quantitative proportion of the prepared porous carbon bundle length may also have a small difference due to the difference in raw materials and processing processes; for example, the quantitative proportion of porous carbon bundles in the same length range may have an absolute difference of no more than ±2%. Similarly, the quantitative ratio of nano-carbon tubes and micro-carbon tubes in the porous carbon bundle and the cross-sectional diameter of the porous carbon bundle are also mainly related to the grinding time and the grinding speed, and similar situations also exist.
[0269] The preparation parameters of the above-mentioned embodiments and comparative examples and the structural parameters of the porous carbon bundle are shown in Table 1 respectively.
[0270] Table 1
[0271]
[0272]
[0273]
[0274] Wherein, T represents the temperature of carbonization treatment, n1 represents the proportion of porous carbon bundles with a length of less than 1 μm in the negative electrode active material for secondary batteries, n2 represents the proportion of porous carbon bundles with a length of 1 μm-10 μm in the negative electrode active material for secondary batteries, n3 represents the proportion of porous carbon bundles with a length of 10 μm-30 μm in the negative electrode active material for secondary batteries, n4 represents the proportion of porous carbon bundles with a length of more than 30 μm in the negative electrode active material for secondary batteries, n5 represents the ratio of nano-carbon tubes to micro-carbon tubes in the porous carbon bundles, d represents the cross-sectional diameter of the porous carbon bundles, w1 represents the mass proportion of the porous carbon bundles in the positive electrode sheet, w2 represents the mass proportion of the first conductive agent in the positive electrode sheet, a represents the mass ratio of the porous carbon bundles to the first conductive agent in the positive electrode sheet; w3 represents the mass proportion of the porous carbon bundles in the negative electrode sheet, w4 represents the mass proportion of the first conductive agent in the negative electrode sheet, and b represents the mass ratio of the porous carbon bundles to the first conductive agent in the negative electrode sheet.
[0275] It should be noted that the above-mentioned ratios of the number of porous carbon bundles of different carbon bundle lengths and the ratios of the number of carbon nanotubes and carbon microtubes in the porous carbon bundles are measured by the following method:
[0276] 1) Build the measurement optical path and collect data: Use a semiconductor laser with vertical polarization as the light source. The laser is focused along the x direction through a lens into the sample pool containing the porous carbon beam solution. The sample particles irradiated by the laser beam are scattered, and the scattered light I to be detected is V After passing through two facing pinholes, it shines on the Wollaston prism, which diffuses the light I V Decomposed into vertically polarized scattered light I VV and horizontal direction I VH The polarized scattered light is converted into electrical pulse signals H1 and H2 by the photomultiplier tube and the photomultiplier tube, and sent to the photon counting card for counting, while recording the scattering angle θ at this time;
[0277] 2) changing the incident direction of the laser irradiating the sample cell in a clockwise direction, that is, changing the incident direction of the laser by Δθ, repeating step 1) to collect data, collecting scattered light signals under different scattering conditions, and recording the corresponding scattering angles;
[0278] 3) Calculate the diameter and length of the porous carbon bundle:
[0279] A: The expression of the scattered light intensity autocorrelation function is as follows:
[0280]
[0281] Where τ is the correlation time, I(t) and I(t-τ) are the scattered light intensities at time t and time t-τ respectively, and n(t) and n(t-τ) are the numbers of scattered photons at the two times;
[0282] According to the expression, the experimental data is substituted into the obtained expression to obtain the scattered light intensity autocorrelation functions GVV-θ(τ) and GVH-θ(τ) in two directions when the scattering angle is θ;
[0283] B: The scattered light autocorrelation function is an exponential decay function, which is in the following form. GVV-θ(τ) and GVH-θ(τ) are fitted by exponential fitting to obtain the decay line widths ΓVV-θ and ΓVH-θ of the scattered light intensity autocorrelation function in the two directions.
[0284]
[0285] C: According to the relationship between Rayleigh line width and translation coefficient DT and rotation coefficient DR, calculate the translation coefficient DT and rotation coefficient DR:
[0286]
[0287] Where q(θ) is the scattering vector, and its calculation formula is as follows:
[0288]
[0289] Where n is the refractive index of the solution, λ0 is the wavelength of the incident light, and θ is the scattering angle;
[0290] D: Since the translation coefficient DT and the rotation coefficient DR satisfy the following formula with the diameter d and the length L of the porous carbon bundle:
[0291]
[0292]
[0293] Where L is the length of the porous carbon bundle, d is the diameter of the porous carbon bundle, and k B is the Boltzmann constant, T is the absolute temperature, η s is the viscosity coefficient of the dispersion medium, which can be obtained by looking up the table. According to the above formula, the diameter d and length L of the porous carbon bundle are calculated;
[0294] 4) Data analysis and processing: Process the data results of the porous carbon bundle diameter and length calculated at different scattering angles θ to obtain the accurate diameter and length of the porous carbon bundle;
[0295] The specific steps of data analysis and processing are as follows:
[0296] 1) Obtaining the autocorrelation function of the collected scattered light signal. Since the depolarized scattered light signal decays faster than the polarized scattered light signal, the decay rate of the autocorrelation function is analyzed to determine whether there is an error in the collected signal;
[0297] 2) Compare the decay rates of the autocorrelation function of polarized scattered light and the autocorrelation function of depolarized scattered light at different scattering angles. The larger the sine value of the scattering angle, the greater the decay rate of the autocorrelation.
[0298] 3) Measure multiple groups of scattering vectors q(θ) at different scattering angles, and the attenuation line width Γ of the scattered light autocorrelation function VV-θ and Γ VH-θ , according to the Rayleigh line width and translation coefficient D T and the rotation coefficient D R The relationship between q(θ) is solved by the least square method. 2 and Γ VV-θ , Γ VH-θ Linear analysis: The translation coefficient D of the porous carbon bundle is obtained by linear analysis. R and the rotation coefficient D T , thus obtaining the diameter and length of the porous carbon bundle;
[0299] 4) Repeat the experimental steps 1)-3) 10 times, analyze and process the data to obtain 10 sets of measurement results, and calculate the average value of the 10 sets of data <l>and <d>, as the final result, the standard deviation of the experimental measurement repeatability is calculated according to the following formula,
[0300]
[0301] formula: <x>is the average of N experimental measurement results, where N is the number of experiments;
[0302] After measuring the diameter of each carbon bundle, statistics are performed to further obtain the number ratio of nano-carbon tubes to micro-carbon tubes in the porous carbon bundle;
[0303] After measuring the length of each carbon bundle, statistics are performed to further obtain the proportion of porous carbon bundles with different carbon bundle lengths.
[0304] The powder resistivity of the porous carbon bundle mentioned above is measured using a powder resistance meter.
[0305] The cross-sectional diameter of the porous carbon bundle mentioned above is measured by scanning electron microscopy (SEM).
[0306] 2. Secondary battery performance test
[0307] 1.Charge rate performance test
[0308] In a constant temperature box at 25℃, the battery is charged from 0% SOC to a cut-off voltage of 3.65V at a constant current of 3C rate, and then charged at a constant voltage of 3.65V until the current is less than 0.05C. The ratio of the charged capacity to the designed capacity in this process is the capacity retention rate at the 3C charging rate.
[0309] In a 25℃ constant temperature box, the battery is charged from 0% SOC to a cut-off voltage of 3.65V at a constant current of 1 / 3C, and then charged at a constant voltage of 3.65V until the current is less than 0.05C. The ratio of the charged capacity to the designed capacity in this process is the capacity retention rate at a charging rate of 1 / 3C.
[0310] 2. Discharge rate test
[0311] In a 25℃ constant temperature box, the battery is discharged from 100% SOC to a cut-off voltage of 2.5V at a constant current of 2C rate. The ratio of the discharged capacity to the designed capacity in this process is the capacity retention rate at 2C discharge rate.
[0312] In a 25℃ constant temperature box, the battery is discharged from 100% SOC to a cut-off voltage of 2.5V at a constant current of 1 / 3C rate. The ratio of the discharged capacity to the designed capacity in this process is the capacity retention rate at 1 / 3C discharge rate.
[0313] The performance test results of the above embodiments and comparative examples are shown in Table 2.
[0314] Table 2
[0315]
[0316]
[0317] From the comparison of the results of Examples 1-28 and Comparative Example 1, it can be seen that the porous carbon bundle provided in the present application can significantly improve the kinetic performance of the secondary battery. The above description of each embodiment tends to emphasize the differences between the embodiments, and the same or similar aspects can be referenced to each other. For the sake of brevity, this article will not repeat them.
[0318] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.< / x> < / d> < / l> < / x> < / d> < / l>
Claims
1. A negative electrode active material for a secondary battery, characterized in that: The porous carbon bundle comprises micro-carbon tubes and nano-carbon tubes arranged in a direction perpendicular to the axial direction of the porous carbon bundle.
2. The negative electrode active material for a secondary battery according to claim 1, characterized in that: The length of the porous carbon bundle is 0.01 μm-200 μm.
3. The negative electrode active material for a secondary battery according to any one of claims 1 to 2, characterized in that: The quantity ratio of the nano-carbon tubes to the micro-carbon tubes in the porous carbon bundle is (10-100):1, and can be optionally (20-50):
1.
4. The negative electrode active material for a secondary battery according to any one of claims 1 to 3, characterized in that: The porous carbon bundle has at least one of the following characteristics: (1) The pore size of the carbon nanotubes in the porous carbon bundle is 1 nm-999 nm; (2) The pore size of the micron carbon tubes in the porous carbon bundle is 1 μm-30 μm; (3) The cross-sectional diameter of the porous carbon bundle is 0.01 μm-40 μm, optionally 0.1 μm-30 μm, and further optionally 0.1 μm-10 μm; (4) The powder resistivity of the porous carbon bundle is 10 -3 Ω·m-10 -5 Ω·m.
5. The negative electrode active material for a secondary battery according to any one of claims 1 to 4, characterized in that: The negative electrode active material for secondary batteries comprises one or more of porous carbon bundles with a length less than 1 μm, porous carbon bundles with a length of 1 μm-10 μm, porous carbon bundles with a length of 10 μm-30 μm, and porous carbon bundles with a length greater than 30 μm.
6. The negative electrode active material for a secondary battery according to claim 5, characterized in that: The ratios of the number of porous carbon bundles with a length of less than 1 μm, the number of porous carbon bundles with a length of 1 μm-10 μm, the number of porous carbon bundles with a length of 10 μm-30 μm, and the number of porous carbon bundles with a length of more than 30 μm to the total number of porous carbon bundles contained in the negative electrode active material for a secondary battery are recorded as n1, n2, n3, and n4, respectively, and n1, n2, n3, and n4 satisfy: 0≤n1≤100%, 0≤n2≤100%, 0≤n3≤100%, and 0≤n4≤100%, and n1, n2, n3, and n4 cannot be 0 at the same time; Optionally, n1, n2, n3 and n4 satisfy: 5%≤n1≤40%, 5%≤n2≤60%, 5%≤n3≤50% and 0.1%≤n4≤30%.
7. A method for preparing a negative electrode active material for a secondary battery according to any one of claims 1 to 6, characterized in that: The steps include: Carbonizing the wood raw material; the wood raw material has wood conduits arranged in a direction perpendicular to the axial direction of the wood raw material; The carbonized wood raw material is ground to prepare the negative electrode active material for the secondary battery.
8. The method for preparing a negative electrode active material for a secondary battery according to claim 7, characterized in that: The carbonization treatment includes at least one of the following conditions: (1) The temperature of the carbonization treatment is 700° C.-900° C.; (2) The carbonization treatment time is 2h-12h, and can be 4h-8h; (3) The atmosphere of the carbonization treatment includes an inert gas; Optionally, the atmosphere of the carbonization treatment includes argon.
9. The method for preparing a negative electrode active material for a secondary battery according to any one of claims 7 to 8, characterized in that: The grinding process includes at least one of the following conditions: (1) The rotation speed of the grinding process is ≤300 rpm; (2) The grinding time is ≤ 20 min.
10. The method for preparing a negative electrode active material for a secondary battery according to any one of claims 7 to 9, characterized in that: Before the step of carbonizing the wood raw material, the method further comprises: Using alkali solution to perform alkali treatment on the wood raw material; Optionally, the alkali solution includes at least one of a sodium hydroxide solution and a potassium hydroxide solution; Optionally, the concentration of the alkali solution is 0.1mol / L-0.3mol / L; Optionally, the alkali treatment time is 18h-30h.
11. The method for preparing a negative electrode active material for a secondary battery according to any one of claims 7 to 10, characterized in that: The wood raw material includes tree blocks.
12. A positive electrode sheet, characterized in that: The positive electrode sheet includes a positive electrode active material layer, and the positive electrode active material layer contains at least one of the negative electrode active material for a secondary battery according to any one of claims 1 to 6 and the negative electrode active material for a secondary battery prepared by the method according to any one of claims 7 to 11.
13. The positive electrode sheet according to claim 12, characterized in that: The positive electrode active material layer further comprises a first conductive agent; Optionally, the first conductive agent includes a zero-dimensional conductive agent; Further optionally, the positive electrode active material layer has at least one of the following characteristics: (1) The mass ratio of the negative electrode active material for secondary battery contained in the positive electrode active material layer to the first conductive agent is 1:(2-4); (2) The total mass proportion of the negative electrode active material for secondary battery and the first conductive agent contained in the positive electrode active material layer is 1% to 10%; (3) The first conductive agent includes a point-shaped contact conductive agent; Optionally, the first conductive agent includes one or more of conductive carbon black, acetylene black and Ketjen black.
14. The positive electrode sheet according to any one of claims 12 to 13, characterized in that: The positive electrode sheet has at least one of the following characteristics: (1) The thickness of the positive electrode active material layer is ≥ 0.01 mm, and can be 0.05 mm-0.3 mm; (2) The coating unit surface density of the positive electrode sheet is ≥ 0.1g / 1540.25mm 2 , optional: 0.16g / 1540.25mm 2 -0.5g / 1540.25mm 2 .
15. A negative electrode plate, characterized in that: The negative electrode sheet includes a negative electrode active material layer, and the negative electrode active material layer contains at least one of the negative electrode active material for a secondary battery according to any one of claims 1 to 6 and the negative electrode active material for a secondary battery prepared by the method according to any one of claims 7 to 11.
16. The negative electrode sheet according to claim 15, characterized in that: The negative electrode active material layer further comprises a second conductive agent; Optionally, the second conductive agent includes a zero-dimensional conductive agent; Further optionally, the negative electrode active material layer has at least one of the following characteristics: (1) The mass ratio of the negative electrode active material for secondary battery and the second conductive agent contained in the negative electrode active material layer is (3-6):1; (2) The total mass proportion of the negative electrode active material for secondary battery and the second conductive agent contained in the negative electrode active material layer is 0.1%-10%; (3) the second conductive agent includes a point-shaped contact conductive agent; Optionally, the second conductive agent includes one or more of conductive carbon black, acetylene black and Ketjen black.
17. The negative electrode sheet according to any one of claims 15 to 16, characterized in that: The negative electrode plate has at least one of the following characteristics: (1) The thickness of the negative electrode active material layer is ≥ 0.01 mm, and can be selected to be 0.1 mm-0.3 mm; (2) The coating unit surface density of the negative electrode sheet is ≥ 0.05g / 1540.25mm 2 , optional: 0.16g / 1540.25mm 2 -0.5g / 1540.25mm 2 .
18. A secondary battery, characterized in that: It comprises at least one of the positive electrode sheet as described in any one of claims 12 to 14 and the negative electrode sheet as described in any one of claims 15 to 17.
19. The secondary battery according to claim 18, wherein: The secondary battery includes at least one of a lithium ion battery and a sodium ion battery.
20. An electrical device, characterized in that: Comprising the secondary battery as claimed in any one of claims 18 to 19.